Acceptance Factors for In-Hospital Pharmacist Interventions in Daily Practice: A Retrospective Study - Durand, Amaury; Gillibert, André; Membre, Sophie; Mondet, Lisa; Lenglet, Aurélie; Mary, Aurélien (Frontiers in Pharmacology, 2022)
INTRODUCTION: Performing pharmacist interventions (PIs) during the medication review helps to improve the quality of care. The acceptance by the physician of these PIs is a good indicator of the quality of this clinical pharmacy activity. The objective of this study was to determine, in the Amiens-Picardie teaching hospital (France), factors of acceptance in a variable environment of activity (central pharmacy, in the care units, computer assisted). METHODS: All PIs transcribed by pharmacists on the Act-IP© site between November 2018 and April 2019 were analyzed using a complementary search in patient records. The environment, type, and clinical impact on patient health of each PI was collected. Linear mixed-effects models with a random pharmacist intercept were used to investigate the relationship between PI modalities and their chance of being accepted. RESULTS: A total of 3 100 PIs were traced, of which 2 930 had been followed over time. Of these, 2 930 PIs, 1 504 (51.3%) were performed by a postgraduate pharmacist and 1 426 (48.7%) by a pharmacy resident, 1 623 (55.4%) were performed by verbal exchange, 455 (15.5%) by telephone, 846 (28.9%) by computer software, and 6 (0.2%) by paper. The clinical impact on patient health was major for 976 PIs (33.3%) and vital for 26 PIs (0.9%). According to the Anatomical Therapeutic Chemical Classification (ATC), they were mainly related to anti-infectives (30.3%), the nervous system (18.7%), and blood and blood-forming organs (17.3%). In total, 2 415 PIs (82.4%) were accepted. According to the multivariate model, a PI was more often accepted when it was transmitted orally rather than by software (+27.7%, 95% CI: +23.2 to +32.1%) and when it was transmitted to a medical resident rather than a postgraduate physician (+4.4%, 95% CI: 1.2 to 7.6%). In these cases, there was a major rather than a moderate clinical impact on patient health (+4.3%, 95% CI: +1.1 to +7.6%). CONCLUSION: This study highlights the importance of the quality of the exchange with the prescriber and the prioritization of high-risk interventions as key points of medication review to improve rate of pharmacist interventions accepted by physician.